2014
DOI: 10.1248/cpb.c14-00190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Variables on the Drucker–Prager Cap Model and Residual Stress Distribution of Tablets Estimated by the Finite Element Method

Abstract: A multivariate statistical technique was applied to clarify the causal correlation between variables in the manufacturing process and the residual stress distribution of tablets. Theophylline tablets were prepared according to a Box-Behnken design using the wet granulation method. Water amounts (X 1 ), kneading time (X 2 ), lubricant-mixing time (X 3 ), and compression force (X 4 ) were selected as design variables. The DruckerPrager cap (DPC) model was selected as the method for modeling the mechanical behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The largest number of the presented studies (35.6% of the total) deal with the stress/density distribution within the tablet during compression [ 5 , 15 , 27 , 61 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. From these, 31.3% deal with the effect of punch shape [ 61 , 74 , 79 , 82 , 85 ].…”
Section: Application Of Fea Modelling For Pharmaceutical Tabletsmentioning
confidence: 99%
“…The largest number of the presented studies (35.6% of the total) deal with the stress/density distribution within the tablet during compression [ 5 , 15 , 27 , 61 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. From these, 31.3% deal with the effect of punch shape [ 61 , 74 , 79 , 82 , 85 ].…”
Section: Application Of Fea Modelling For Pharmaceutical Tabletsmentioning
confidence: 99%
“…It should be noted that all the above reviewed work only use the DP model without the elliptical cap to simulate granular flow. The Modified Drucker–Prager/Cap (MDPC) model with density dependence is generally used to model powder compaction and pharmaceutical tablet manufacture. A few work of soil shear , and ice gouging used MDPC model for analysis. A recent work by Jin et al demonstrated that the MDPC model, with rigorous calibration, can be used to model the quasi-static flow behavior of ground loblolly pine as shown in Figure .…”
Section: Constitutive Modelsmentioning
confidence: 99%
“…However, relatively little information is available in the literature on experimental studies of mechanical kneading process on the physicochemical properties of plastic lubricants. Authors (Hayashi et al 2014) theoretically studied the influence of mechanical kneading on the occurrence of residual stresses during tableting by means of finite element methods (FEM) analysis. That is why this experimental study focussed on the effect of rapeseed oil additive on thermal and rheological properties of commercial lubricants by means of thermal analysis, rotational vis-cometry, a novel vibration damping technique and pressure drop measurements.…”
Section: )mentioning
confidence: 99%